Invariant phase structure of olivo-cerebellar oscillations and its putative role in temporal pattern generation - Jacobson, Gilad A; Lev, Iddo; Yarom, Yosef; Cohen, Dana (Proceedings of the National Academy of Sciences - PNAS, 2009)
Complex movements require accurate temporal coordination between their components. The temporal acuity of such coordination has been attributed to an internal clock signal provided by inferior olivary oscillations. However, a clock signal can produce only time intervals that are multiples of the cycle duration. Because olivary oscillations are in the range of 5-10 Hz, they can support intervals of [almost equal to]100-200 ms, significantly longer than intervals suggested by behavioral studies. Here, we provide evidence that by generating nonzero-phase differences, olivary oscillations can support intervals shorter than the cycle period. Chronically implanted multielectrode arrays were used to monitor the activity of the cerebellar cortex in freely moving rats. Harmaline was administered to accentuate the oscillatory properties of the inferior olive. Olivary-induced oscillations were observed on most electrodes with a similar frequency. Most importantly, oscillations in different recording sites retained a constant phase difference that assumed a variety of values in the range of 0-180°, and were maintained across large global changes in the oscillation frequency. The inferior olive may thus underlie not only rhythmic activity and synchronization, but also temporal patterns that require intervals shorter than the cycle duration. The maintenance of phase differences across frequency changes enables the olivo-cerebellar system to replay temporal patterns at different rates without distortion, allowing the execution of tasks at different speeds.